Penerapan Metode Weighted Product (WP) Dalam Keputusan Rekomendasi Pemilihan Manager Penjualan - Rizal, Chairul; Siregar, Saidi Ramadan; Supiyandi, Supiyandi; Armasari, Selly; Karim, Abdul (Forum Kerjasama Pendidikan Tinggi, 2021)
The best employees are very important assets for the company, because of that sales companies need a system that can choose the best employees objectively and optimally so that they are right in choosing the best employees who will have an impact on the progress of the company. To be able to solve the problem the author conducted research using a Decision Support System using the Weighted Product (WP) method. The WP method is part of the Multiple Attribute Decision Making (MADM), which requires a normalization process to be calculated. This method in detail calculates the weight of the value of each criterion. The final result of the research shows that the 10th alternative (A10) with a Preference Value of 0.1120 was chosen to be the best employee recommended in the selection of sales manager